2019
DOI: 10.32615/bp.2019.079
|View full text |Cite
|
Sign up to set email alerts
|

Sense- and antisense-mediated resistance against Sri Lankan cassava mosaic virus (SLCMV) in Nicotiana benthamiana

Abstract: Sri Lankan cassava mosaic virus (SLCMV) is the principal causal agent of cassava mosaic disease in the Indian subcontinent. To gain resistance against the virus, the coat protein (CP) gene, namely the AV1 of SLCMV-Adivaram isolate, was cloned in either sense or antisense orientation under the Cauliflower mosaic virus 35S promoter, and transgenic Nicotiana benthamiana plants were obtained through Agrobacterium-mediated transformation. A total of eight T1 transgenic lines, four harboring the CP-sense construct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Subsequent to several evaluation trials of MNga-1 (a breeding line from IITA) in the field conditions of India, CTCRI has released a variety named Sree Padmanabha in the state of Tamil Nadu, which showed high-level resistance to ICMV and SLCMV, and has been used in developing resistant clones through intervarietal hybridization (Nair et al, 1998;Unnikrishnan et al, 2002;Abraham et al, 2006;George et al, 2012). In addition, evaluation of the MNga-1 seedling population yielded CMR1 and CMR129 with CMD resistance and high starch content (Unnikrishnan et al, 2011).…”
Section: Breeding For Cmd Resistancementioning
confidence: 99%
“…Subsequent to several evaluation trials of MNga-1 (a breeding line from IITA) in the field conditions of India, CTCRI has released a variety named Sree Padmanabha in the state of Tamil Nadu, which showed high-level resistance to ICMV and SLCMV, and has been used in developing resistant clones through intervarietal hybridization (Nair et al, 1998;Unnikrishnan et al, 2002;Abraham et al, 2006;George et al, 2012). In addition, evaluation of the MNga-1 seedling population yielded CMR1 and CMR129 with CMD resistance and high starch content (Unnikrishnan et al, 2011).…”
Section: Breeding For Cmd Resistancementioning
confidence: 99%
“…Similarly, tobacco plants transformed with hpRNA containing CP gene of TSV through the Agrobacterium, mediated transformation exhibited resistance to TSV upon mechanical inoculation and ELISA confirmed the lower level of virus titre in transgenic tobacco lines (Rajamanickam et al, 2015a). Gogoi et al (2019) found that transgenic tobacco plant expressing sense and antisense orientation of CP gene of Sri Lankan cassava mosaic virus (SLCMV) showed resistance to SLCMV. The Northern blot analysis of tobacco line confirmed the expression of virus specific siRNAs, indicated that RNA silencing technology has been adopted in virus resistance.…”
Section: Figure 1 Schematic Representation Of Rnai Mechanism In Plantsmentioning
confidence: 99%
“…In pathogen-derived resistance (PDR), a portion or full viral genome is inserted into a plant; thereafter, it regulates or interferes with vital steps in the life cycle of the pathogen,which led to resistance in plants against virus infection. Diverse viral pathogen-derived genes such as coat protein, movement protein and replicase genes have been effectively utilized to buildout the virus-resistant transformants (Baulcombe, 2002;Senthilraja et al, 2018;Gogoi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cassava ( Manihot esculenta Crantz) is the third most common plant-based carbohydrate source after rice and maize [ 1 ]. It is used for human consumption, animal feed, and plant-based energy production.…”
Section: Introductionmentioning
confidence: 99%